Chronic Sublethal Aluminum Exposure and Avena fatua Caryopsis Colonization Influence Gene Expression of Fusarium avenaceum F.a.1 - Lewis, Ricky W.; Okubara, Patricia A.; Fuerst, E. Patrick; He, Ruifeng; Gang, David; Sullivan, Tarah S. (Frontiers in Microbiology, 2020)
Fusarium avenaceum F.a.1 is a novel strain of a fungal plant pathogen capable of preferentially decaying wild oat (Avena fatua) caryopses compared with those of wheat (Triticum aestivum). Understanding the molecular mechanisms governing weed seed-pathogen interactions is crucial to developing novel weed seed suppression technologies. Additionally, wild oat often competes with wheat in regions undergoing soil acidification, which leads to increases in soluble concentrations of many metals, including aluminum (Al). A transcriptomic approach was used to investigate molecular responses of F.a.1 during wild oat caryopsis colonization in the presence and absence of chronic, sublethal concentrations of Al (400 µM). Caryopsis colonization was associated with induction of genes related to virulence, development, iron metabolism, oxidoreduction, stress, and detoxification, along with repression of genes associated with development, transport, cell-wall turnover, and virulence. Caryopsis colonization during Al exposure resulted in the induction of genes associated with virulence, detoxification, stress, iron metabolism, oxidoreduction, and cell wall turnover, along with repression of genes associated with cell wall metabolism, virulence, development, detoxification, stress, and transcriptional regulation. Aluminum exposure in the absence of caryopses was associated with induction of genes involved in siderophore biosynthesis, secretion, uptake, and utilization, along with several other iron metabolism-related and organic acid metabolism-related genes. The siderophore-related responses associated with Al toxicity occurred concurrently with differential regulation of genes indicating disruption of iron homeostasis. These findings suggest Al toxicity is attenuated by siderophore metabolism in F.a.1. In summary, both caryopsis colonization and Al toxicity uniquely influence transcriptomic responses of F.a.1.